Follow-Up: A Neglected Experiential Process within a Transformational Learning Community for Teachers as Adult Learners during the Pandemic - Tzovla, Eirini; Kedraka, Katerina (Adult Education Critical Issues, 2023)
This article refers to an effort to transform the views and attitudes of a group of teachers, who participated in a distance professional development program during the pandemic period, which was about the use of digital educational content in the teaching practice. The program adopted in its design and implementation elements from different models of professional development taking into account the educational needs of the participants as they had been expressed in relevant research that had preceded it. In terms of methodology, Mezirow's 10 steps of transformation were followed. The results showed a transformation of the perceptions and attitudes of the participants regarding the utilization of digital educational content in educational practice.